Clinical efficacy of cord blood platelet gel in chronic limb-threatening ischaemia patients: a case series - Mastrangelo, Giovanni; Santodirocco, Michele; Semerano, Luigi; Palena, Giancarlo; Sciannelli, Vincenzo; Magistro, Gabriele; Marinucci, Roberto; Di Sebastiano, Pierluigi; Palazzo, Vincenzo (Italian Journal of Anatomy and Embryology, 2023)
The cord blood platelet gel (CBPG), rich in growth factors and chemoattractans molecules, is a useful tool to treat lesions with tissue loss as it accelerates remission and ensures the functional recovery of the limb. The results obtained in a series of 10 patients treated at the “Fondazione IRCCS Casa Sollievo della Sofferenza” in San Giovanni Rotondo (Italy) with CBPG in the treatment of revascularized patients with chronic limb-threatening ischemia (CLTI) are presented here. In the period 2017-2021, they were treated with surgical toileting of the ulcers and application of CBPG. As a general scheme, CBPG was applied once every 21 days for 3 times; 8 out of 10 patients observed had diabetes mellitus, of these 4 were on insulin therapy. One patient underwent a major amputation; two patients died for non-infectious causes. Studies in the literature show that CBPG is safe for patients affected by CLTI and undergoing revascularization, promoting faster healing. Our results appear to overlap this data, also showing CBPG as an effective therapeutic option for the treatment of vascularized patients with foot lesions for CLTI, reducing the risk of major amputation. In perspective, multicenter randomized studies are needed to evaluate immediate and late results.